2022
DOI: 10.1039/d2mo00004k
|View full text |Cite
|
Sign up to set email alerts
|

Mass spectrometry-based proteomics in neurodegenerative lysosomal storage disorders

Abstract: The major function of the lysosome is to degrade unwanted materials such as lipids, proteins, and nucleic acids; therefore, deficits of the lysosomal system can result in improper degradation and...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 255 publications
0
3
0
Order By: Relevance
“… 40 Additionally, the upregulation of lysosomal proteins was commonly reported in other lysosomal storage disorders, such as NPC, Gaucher, mucopolysaccharidoses, and others, and is thought to represent a compensatory mechanism for impaired lysosomal function. 41 , 42 , 43 In line with these previous findings, proteomics analysis of whole cortical tissue in this study showed similar upregulation of the lysosomal protein signature in saline-treated Mcoln1 −/− mice, and CPP16-mediated MCOLN1 gene transfer resulted in the broad correction of the lysosomal protein signature, providing an additional evidence of the treatment efficacy on the molecular level.…”
Section: Discussionsupporting
confidence: 90%
“… 40 Additionally, the upregulation of lysosomal proteins was commonly reported in other lysosomal storage disorders, such as NPC, Gaucher, mucopolysaccharidoses, and others, and is thought to represent a compensatory mechanism for impaired lysosomal function. 41 , 42 , 43 In line with these previous findings, proteomics analysis of whole cortical tissue in this study showed similar upregulation of the lysosomal protein signature in saline-treated Mcoln1 −/− mice, and CPP16-mediated MCOLN1 gene transfer resulted in the broad correction of the lysosomal protein signature, providing an additional evidence of the treatment efficacy on the molecular level.…”
Section: Discussionsupporting
confidence: 90%
“…We report broad upregulation of lysosomal enzymes and structural lysosomal proteins in whole tissue homogenates from Mcoln1 −/− mice, with two of the detected lysosomal enzymes commonly upregulated in whole brain and isolated brain cell data sets ( Figures 2 , 4B ). Using various techniques, including transcriptomics, immunohistochemistry, and enzymatic activity assays, upregulation of lysosomal proteins was commonly reported in other lysosomal storage disorders, such as NPC, Gaucher, mucopolysaccharidoses, and others, and is thought to represent a mechanism to compensate for impaired lysosomal function ( Platt et al, 2012 ; Parenti et al, 2021 ; Li and Cologna, 2022 ). A similar increase of lysosomal proteins was reported in the single MLIV brain autopsy proteome, highlighting the universal nature of these observations in the brain tissue across species ( Vardi et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…To gain an understanding of the mechanisms of NPC, there have been notable efforts to compare the proteomes between control and NPC brains using various models, as reviewed in ref . Studies have been carried out in the cerebellum, cerebral cortex, corpus callosum, and hippocampal regions, comparing Npc1 –/– and wild-type mice across different ages. From these studies, changes in proteins playing roles in the formation of multivesicular bodies, endosomal/lysosomal systems, nonendocannabinoid hydrolases, fatty-acid and cholesterol transport, autophagy, calcium regulation, and Rho-family GTPases signaling were recorded. ,,, Despite numerous studies, multiple questions regarding NPC remain unanswered including protein phosphorylation-specific changes, protein expression within noncerebellar brain regions, and the mechanisms leading to neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%
“…8 Notably, a hallmark of this disease is the progressive degeneration of Purkinje neurons in the cerebellum. 9 To gain an understanding of the mechanisms of NPC, there have been notable efforts to compare the proteomes between control and NPC brains using various models, as reviewed in ref 10. Studies have been carried out in the cerebellum, cerebral cortex, corpus callosum, and hippocampal regions, comparing Npc1 −/− and wild-type mice across different ages.…”
Section: ■ Introductionmentioning
confidence: 99%